CO2 biogeochemical investigation and microbial characterization of red wood ant mounds in a Southern Europe montane forest. (March 2022) - Balzani, Paride; Masoni, Alberto; Venturi, Stefania; Frizzi, Filippo; Bambi, Marina; Fani, Renato; Nisi, Barbara; Tassi, Franco; Vaselli, Orlando; Zaccaroni, Marco; Santini, Giacomo
Abstract: Red wood ants are ecologically important species in Europe that form large colonies. Their nest mounds are characterized by stable microclimatic conditions, that are favourable to the development of rich invertebrate and microbial communities. Through their respiration processes, all these inhabitants contribute to the total gas emissions of the mounds. Quantifications of red wood ant mounds CO2 production are only available from Northern and Central Europe, and the Alps, where these ants are common. During the second half of the last century some species were transplanted from the Alps to southernmost sites, where they were not present, to be employed as biocontrol agents. No information on the contribution of these low-latitudes populations to the local forest CO2 production is available. The microbial communities living within red wood ant mounds are also poorly known. In this study, we investigated the CO2 gas emissions and the microbiome of the mounds of an introduced population of the red wood ant Formica paralugubris in a Southern Europe montane forest. We found that ant mounds produced more CO2 than the forest soil, and that their CO2 efflux as well as internal concentration were higher during summer than winter, with a lighter CO2 carbon isotopic signature in summer than winter, likely due to an increased ant activity. Moreover, the top part of the mound was characterised by higher CO2 efflux and lower CO2 internal concentration compared to the bottom, probably due to its internal structure and conditions. The isotopic signature of the mound material was similar between summer and winter, suggesting a metabolic similarity of the microbial communities. Also, we estimated the ants' relative contribution to the total mound CO2 production to be 83%, whereas the microbiota CO2 contribution was estimated at 17%. Finally, the mound microbiome composition varied between summer and winter, though no seasonal difference in the diversity indexes or β-diversity was found. Our results demonstrate the impacts of the introduced red wood ants on the carbon dynamics of the recipient ecosystem. Highlights: Red wood ant mounds are hotspot of CO2 emission, producing more than forest soil. CO2 parameters presented seasonal and topological differences within the mounds. Ants contributed 83%, while microbiota 17%, to the total mound CO2 production. The microbiota varied taxonomically but not metabolically between seasons. The microbiota diversity indexes were similar between seasons.